A grand gesture: Vocal and corporeal control in rhythm, music and emotion - Morley, I (Oxford University Press, 2012)
Fitch’s paper represents a timely enquiry into the rhythmic dimension of music origins, an aspect which has to date received far less attention than the tonal elements of musical behaviours. In particular, investigations into the relationships between musical and linguistic capabilities have often focused most on those elements which share the trait of vocal production — meaning, in the case of music, the production and perception of pitch and contour, and the structures within them. The research cited by Fitch in this paper and his own related ideas represent welcome additions to such investigations. It is increasingly evident that the rhythmic, gestural, expressive, and tonal production and perception systems are intimately related and interdependent, and any future considerations of music origins that do not consider all of these dimensions as integral to the emergence of the capacity will be incomplete. There is far more of importance in Fitch’s paper than it is possible to comment on here, so I must be selective and draw out just a few aspects to which I can immediately respond and which, in my opinion, raise particular queries for further elaboration. I then will respond in detail to one key point of interest raised in Fitch’s paper — the relationship(s) between rhythm, melody, and corporeal motor control.